Female authority : empowering women through psychotherapy - Young-Eisendrath, Polly; Wiedemann, Florence L (Guilford Press, 1987)
For women in Western society, there is no straightforward path of development to autonomous adulthood. The double-bind of female authority--that a women cannot be both a healthy adult and an ideal woman-- is the context in which a woman must construct her self in this culture. Whether she sees herself as \"too needy\" or \"too controlling,\" \"too insecure\" or \"too self-reliant,\" she is gathering evidence to support a theory of personal inadequacy. The traditional perspectives of psychodynamics and psychopathology reinforce women\'s sense of inferiority. How then does a woman claim her own authority-- the validity of her own truth, beauty, goodness, originating in her own experience. Young-Eisendrath and Wiedemann break with the tradition of \"deficit thinking,\" the examination of what is absent, wrong, or deficient. Recognizing this as a fundamental barrier to the empowerment of women, they work instead from an understanding of what is already strong and satisfying in the lives of women and girls in a patriarchal society. This volume unravels the paradox of female authority through the examination of its sociocultural, symbolic, and personal dimensions. Chapters 1 through 4 present a re-visioning of the female self, using the psychologies of C. G. Jung and Jane Loevinger as major theoretical frameworks. The authors argue for a modification of Jung\'s concept of \"animus\' --the repressed masculine in the girl or woman--and in chapters 5 through 8 present a detailed model of psychotherapy based on five stages of animus development. Using a wealth of clinical material from their own practices --including two extended case presentations in chapters 9 through 11-- the authors skillfully illustrate their own efforts to help women assume greater personal authority. The book\'s concluding chapter presents New Texts and Contexts for Female Development. Unique in its combination of feminist theory, social psychology, and Jungian psychology, FEMALE AUTHORITY offers a fresh approach to the analysis of gender concerns in identity. The book will be of great value to practitioners and theoreticians in the human services. The discussion of women\'s self-esteem and personal authority, and the probing of conflicts inherent in female identity in our society, place this book among the major recent contributions to the development of a psychology of women.
Keywords: Mental Disorders; zdraví žen; psychiatrie; Mental Health; duševní zdraví; psychoterapie; Women's Health; Psychotherapy; ženská práva; Women's Rights; duševní poruchy